1976
DOI: 10.1093/jnci/56.5.1035
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Antibodies and Immunoglobulin Class and Subclass Levels in Corynebacterium Parvum -Treated Mice

Abstract: Changes in immunoglobulin class and subclass levels and the development of antitumor antibodies were assessed in normal and tumor-bearing mice challenged with Corynebacterium parvum. C. parvum administration resulted in a marked increase in certain immunoglobulin levels, especially Ig G2b, and in the development of antibodies reacting with syngeneic and allogeneic tumor cells. The serologic changes induced by C. parvum were dependent on the dose and route of administration; preliminary studies suggested that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1977
1977
1989
1989

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…shown that the administration of C. parvum to both mouse and man results in a marked increase in the levels of certain immunoglobulin classes and subclasses (James et al, 1975;James et al, 1976). Furthermore, this treatment in mice is accompanied by an increase in the levels of circulating immunoglobulin capable of binding to tumor cells in vitro .…”
Section: Extensive Studiesmentioning
confidence: 99%
“…shown that the administration of C. parvum to both mouse and man results in a marked increase in the levels of certain immunoglobulin classes and subclasses (James et al, 1975;James et al, 1976). Furthermore, this treatment in mice is accompanied by an increase in the levels of circulating immunoglobulin capable of binding to tumor cells in vitro .…”
Section: Extensive Studiesmentioning
confidence: 99%
“…Thus, whilst C. parvum therapy consistently caused a significant increase in the levels of tumour IgA and IgM, it rarely elicited a significant increase in IgG2a and IgG2b. These effects contrast with those observed with respect to serum immunoglobulin levels were the same C. parvumn protocol increases the level of all classes and subclasses, but especially IgG2a and IgG2b (James et al, 1976;1977). Whilst these differences suggest selective binding or local production of certain immunoglobulins by infiltrating host cells, these possibilities have still to be investigated.…”
Section: Discussionmentioning
confidence: 78%
“…4). However, differences in the 16-3+ 6-9 ;ted 102-3 + 38-9 6-3 + 0-9 4-9+0-9 4-3 + 0-8 5-5+0-9 2-3+0-6 2-9+0-1 2-6+0-1 2 4 + 02 2-5+0-3 2-1+0-2 3-7+0-3 16-2+2-0 6-6+0-8 15-8 + 1-0 7-6 + 1-7 12-6 + 2-0 6-8 + 1-0 13-8+2-0 5-8+0-8 12-4+1-1 <1 10-8+0-7 6-1+0-9 105+0-8 <1 10-0+0-9 <1 9-1+0-9 <1 10-7+ 1-1 James et al, 1976). Experiments were therefore performed to ascertain whether C. parvum treatment might influence the amount of immunoglobulin associated with solid tumours in vivo.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that BCG shares com mon antigens with a number of different tumor cells including guinea pig hepatoma, Rous sarcoma and hu man melanoma [10][11][12][13][14][15]. Antigens common to C. par vum and to 3-methylcholanthrene-induced fibrosarcoma in mice have been described [16]. Shared antigenicity between the purified line-10 guinea pig hepatoma and BCG has also been reported [17,18].…”
Section: Discussionmentioning
confidence: 99%